Efektifitas Asuhan Keperawatan Dengan Terapi Aroma Lavender Dalam Mengatasi Insomnia di Wilayah Kerja Puskesmas Sei Panas Batam: Efektifitas Asuhan Keperawatan Dengan Terapi Aroma Lavender Dalam Mengatasi Insomnia di Wilayah Kerja Puskesmas Sei Panas Batam - Larasuci Arini (Jurnal Ilmiah Cerebral Medika, 2020)
Health programs for all ages, one of which is a program for the elderly which aims to increase UHH (life expectancy) in the elderly, namely making the elderly enjoy a happy and useful old age, focusing on promotive and preventive efforts, active participation and participation. Across sectors, health centers as the main key in community movement are expected to make pro-active efforts to work together with community leaders to improve the welfare of the elderly. Insomnia is a sleep disorder that is often complained of by the elderly, characterized by difficulty sleeping and maintaining sleep. Insomnia in the elderly is caused by several factors, namely health status, drug use, environmental conditions, psychological stress, diet / nutrition, lifestyle in the elderly. Aromatherapy is a complementary therapy that can be used to treat insomnia. Aromatherapy has a calming or relaxing effect for several disorders such as reducing anxiety, tension and insomnia. The purpose of implementing this nursing care is so that the elderly can overcome insomnia experienced non-pharmacologically using lavender aroma therapy. The method of this research is a case study that uses nursing care including assessment, diagnosis, intervention, implementation and evaluation. The result of this nursing care provision is by giving lavender aroma therapy for 30 minutes, the patient feels relaxed when going to sleep, so that he is considered able to overcome insomnia. Based on the results of this care, lavender aroma therapy is one of the non-pharmacological therapies that is considered effective for treating insomnia in the elderly. In this study, it is expected that families and communities use aromatherapy as an alternative to treat insomnia.